The Expected, Perceived, and Realized Inflation of U.S. Households before and during the COVID-19 Pandemic - Michael Weber; Yuriy Gorodnichenko; Olivier Coibion (Institute of Labor Economics (IZA), 2022)
As the pandemic spread across the U.S., disagreement among U.S. households about inflation expectations surged along with the mean perceived and expected level of inflation. Simultaneously, the inflation experienced by households became more dispersed. Using matched micro data on spending of households and their macroeconomic expectations, we study the link between the inflation experienced by households in their daily shopping and their perceived and expected levels of inflation both before and during the pandemic. In normal times, realized inflation barely differs across observable dimensions but low income, low education, and Black households experienced a larger increase in realized inflation than other households did. Dispersion in realized and perceived inflation explains a large share of the rise in dispersion in inflation expectations.
Keywords: E02; E03; 330; inflation expectations; COVID-19; surveys